Analisis Faktor yang Mempengaruhi Kualitas Tidur Mahasiswa UMPAR - Nur Afifah Sukardi; Milda Juwina; Aisyah Aisyah; Sudirman Sudirman (Media Literasi Indonesia, 2025)
Good sleep quality is very important to support the physical and mental health of students, but there are still many students who experience sleep disorders due to dense academic and social activities. This study aims to analyze the factors that affect the quality of sleep of FIKES students Class 2022, Muhammadiyah University of Parepare. This study used a quantitative descriptive design with a cross sectional approach on 14 students selected by simple random sampling. Data were collected through questionnaires measuring sleep quality, physical activity, sleep patterns, and emotional stress. The results showed that 57.14% of students had good sleep quality, while 42.86% experienced poor sleep quality. Most respondents (64.29%) had low physical activity, 35.71% had poor sleep patterns, and 28.57% experienced high emotional stress. It can be concluded that students' sleep quality is influenced by the level of physical activity, sleep patterns, and emotional stress, so efforts are needed to increase physical activity, manage stress, and habituate healthy sleep patterns to support student productivity and health